Analysis of construction and demolition waste prediction post-earthquake disasters - Ugur Emre Temelli; Naim Sezgin; Bilge Ozdogan Cumali; Semih Nemlioglu (Engineering Science and Technology, an International Journal)
The proper management of construction and demolition wastes (CDWs) involves understanding their origins, generation, and efficient collection methods. This is especially crucial in developing countries experiencing rapid urbanization and industrialization, where new construction and the reconstruction of older, lower-quality buildings are common practices. Governmental encouragement for the reconstruction of weak buildings, often due to dangerous conditions or natural disasters like earthquakes, further contributes to the generation of vast amounts of CDWs. In this study, the masses and volumes of CDWs resulting from the Kahramanmaras and Hatay earthquakes that occurred on February 6th, 2023, and the anticipated Istanbul earthquake in Turkiye were estimated. Additionally, the amounts of mineral fraction wastes (MFWs) and scrap iron wastes (SIWs) within these CDWs were calculated, along with their economic values. The quantitative estimations of waste generation for CDW were determined as 396,473,616 tons and 293,684,160 m3 for Kahramanmaras and Hatay earthquakes, and 393,456,358 tons and 291,449,154 m3 for the anticipated Istanbul earthquake, respectively. The economic values of recyclable materials (MFWs and SIWs) were calculated as €935,677,734 and €1,268,715,571 for Kahramanmaras and Hatay earthquakes, and €928,557,005 and €1,259,060,346 for Istanbul, respectively.